Sustainability in interior design - Moxon, Sian. (London : Laurence King Publishing, 2012)
The environmental impact of interior architecture and design practice is immense. This book highlights the need for designers to adapt the way they work and relearn lessons that have been lost.
Includes bibliographical references (p. 180-181) and index.
Keywords: Interior decoration -- Environmental aspects; Sustainable design